2021
DOI: 10.1186/s12903-020-01379-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of silver diamine fluoride among patients treated in community dental clinics: a naturalistic study

Abstract: Background Silver diamine fluoride (SDF) is a minimally-invasive preventive service used in the U.S. to avert and arrest caries since 2014. No studies document survival outcomes based in real world delivery. We analyzed 12-month survival outcomes of SDF applied independently or concurrently with other restorative procedures among a population receiving community dental care. Methods We analyzed data on SDF applications from de-identified dental cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Our study found that caries arrest was better in group 1, which was reflected by 58.9% of the teeth recording score 1. Similar findings were also reported in studies conducted by Zhi et al, 1 Llodra et al, 10 Fung et al, 23 and Vollú et al 32 The analysis also showed that the survival of the SDF restorations was higher than in the case of ART, and this was similar to the findings of Raskin et al 33 This may be a consequence of the remineralizing effect of SDF without requiring a proper cavity form, technical skills and or the use of complex armamentarium. Due to the abovementioned advantages of SDF, it can be used with little or no training by primary healthcare workers in areas with the shortage of dental manpower.…”
Section: Discussionsupporting
confidence: 87%
“…Our study found that caries arrest was better in group 1, which was reflected by 58.9% of the teeth recording score 1. Similar findings were also reported in studies conducted by Zhi et al, 1 Llodra et al, 10 Fung et al, 23 and Vollú et al 32 The analysis also showed that the survival of the SDF restorations was higher than in the case of ART, and this was similar to the findings of Raskin et al 33 This may be a consequence of the remineralizing effect of SDF without requiring a proper cavity form, technical skills and or the use of complex armamentarium. Due to the abovementioned advantages of SDF, it can be used with little or no training by primary healthcare workers in areas with the shortage of dental manpower.…”
Section: Discussionsupporting
confidence: 87%
“…There is undoubtedly renewed interest in the use of SDF solutions, especially since the COVID-19 pandemic triggered a search for procedures that generate the least amount of aerosols possible 18,19 . The advantages of using SDF solutions are that application time is fast, without the need for cavity preparation, and the product is effective in primary and permanent dentition, making it an important resource, especially for public dental healthcare [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this population-level, real-world study suggests that SDF application is effective in caries arrest. Since the data for the study was drawn from dental claims, the diagnosis for SDF application (e.g., hypersensitivity vs decay, cavitated vs non-cavitated lesions) could not be ascertained and therefore data only represents overall survival rates of SDF application and must be interpreted cautiously [ 63 ].…”
Section: Silver Diamine Fluoridementioning
confidence: 99%